Translating monetary inputs into health care provision: a comparative analysis of the impact of different modes of public policy - Wendt, Claus; Kohl, Jürgen (Journal of comparative policy analysis, 2010)
This article investigates different modes of public policy in health care and their impact on health care financing and health service provision. In order to investigate the relationship between health expenditure and health service provision, we construct an “index of health care providers”. The empirical analysis of expenditure and this index demonstrates that there is only a weak correspondence between the level of total health expenditure and the number of health service providers in OECD countries. Different modes of health policy can help to explain why some countries are more successful in translating monetary inputs into health care personnel than other countries. Our results indicate that policies which favor self-regulation by non-governmental actors (as in Germany) lead in general to high levels of health care providers at above OECD average health expenditure. Policies which favor direct state control (as in the United Kingdom), on the other hand, are characterized by lower levels of health care providers and below average health expenditure. Policies which favor market elements are more difficult to categorize. However, it is noteworthy that especially countries that give market mechanisms higher priority than other countries (as the United States) offer below average numbers of health care providers at comparatively high total health care costs.
Gesehen am 16.11.2023